The spatial patterns of deforestation in the Ko’mara forest area - Rachmawati, Leny; Paembonan, Samuel A.; Rijal, Syamsu; Nursaputra, Munajat; Soma, Andang Suryana; Millang, Syamsuddin; Mujetahid, A. (Jurnal Penelitian Kehutanan Wallacea, 2023)
Land-use changes result from changes in the human population, their activities, and social and environmental activities, which occur in a complex and dynamic manner. The change of forested areas to non-forested areas, also known as deforestation, is a land-use change. Deforestation influences land cover by creating a specific distribution pattern (fragmentation). Almost the entire forest has been fragmented into smaller areas, but the pattern of each of these forest areas is uncertain. As a consequence, it would be more challenging to control potential deforestation. Using the spatial metrics of Clumpiness index, Contiguity index, and Patch density, deforestation in one of the forest areas, namely the Ko'mara forest area, was carried out. This research was analyzed using GIS and Fragstat software in raster data format. The analysis results show that the spatial pattern of deforestation in this area has a clumped distribution, with a high level of patch contiguity and a low to medium level of fragmentation. This pattern represents the form of deforestation in the Ko'mara forest area in 2005-2010 and 2010-2015 was classified as Low Deforestation with a deforestation rate of <1%, but was classified as Moderate Deforestation in 2015-2019 because the value obtained was 1.1%.